Mechanism of Lithium Metal Penetration through Inorganic Solid Electrolytes. Issue 20 (6th July 2017) - Porz, Lukas; Swamy, Tushar; Sheldon, Brian W.; Rettenwander, Daniel; Frömling, Till; Thaman, Henry L.; Berendts, Stefan; Uecker, Reinhard; Carter, W. Craig; Chiang, Yet‐Ming
Abstract: Li deposition is observed and measured on a solid electrolyte in the vicinity of a metallic current collector. Four types of ion‐conducting, inorganic solid electrolytes are tested: Amorphous 70/30 mol% Li2 S‐P2 S5, polycrystalline β‐Li3 PS4, and polycrystalline and single‐crystalline Li6 La3 ZrTaO12 garnet. The nature of lithium plating depends on the proximity of the current collector to defects such as surface cracks and on the current density. Lithium plating penetrates/infiltrates at defects, but only above a critical current density. Eventually, infiltration results in a short circuit between the current collector and the Li‐source (anode). These results do not depend on the electrolytes shear modulus and are thus not consistent with the Monroe–Newman model for "dendrites." The observations suggest that Li‐plating in pre‐existing flaws produces crack‐tip stresses which drive crack propagation, and an electrochemomechanical model of plating‐induced Li infiltration is proposed. Lithium short‐circuits through solid electrolytes occurs through a fundamentally different process than through liquid electrolytes. The onset of Li infiltration depends on solid‐state electrolyte surface morphology, in particular the defect size and density. Abstract : Lithium metal penetration through sulfide and oxide solid electrolytes that have been proposed for use in solid‐state batteries occurs via the extension of pre‐existing surface defects, of sizes down to submicron scale, due to electrodeposition‐induced stresses.